in the article the analysis of advertising and information space by means of outdoor advertising in the Republic of Burundi - Vuganeza F. (Scientific community of students, 2018)
in the article the analysis of advertising and information space by means of outdoor advertising in the Republic of Burundi
Keywords: наружная реклама; рекламно-информационное пространство; outdoor advertising; advertising and information space